2014
DOI: 10.1155/2014/247652
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Visualization of Bilateral Thrombosis in the Posterior Inferior Cerebellar Artery Apparent in the Telovelomedullary Segment

Abstract: Unilateral posterior inferior cerebellar artery (PICA) thrombosis is frequent. However, bilateral PICA thrombosis is rare. Herein we report about an intraoperative visualization of a bilateral thrombosis of the telovelomedullary segment of the PICA. A 74-year-old woman was admitted to our department on day two of a bilateral PICA thrombosis with developing cerebellar infarction. Her Glasgow Coma Scale score dropped from 15 to 13, and cranial computed tomography revealed compression of the fourth ventricle with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In addition, calcium flow from the endoplasmatic reticulum (ER) is highly regulated by Ryanodine receptors, Inositol trisphosphate receptor, calciumdependent kinases, and phosphatases (Brini et al, 2014). Alterations in Ca 2 + homeostasis have been related to the appearance and progression of several NDDs, including AD and PD (Marambaud et al, 2009;Nevzati et al, 2014). Indeed, it has been reported that exposure to either Aβ peptides (Li et al, 2009) or α-synuclein oligomers (Danzer et al, 2007) induces neuronal death by activating Ca 2+ dependent signaling pathways and metabolic derangements (Arundine and Tymianski, 2003), most likely by increasing mitochondrial Ca 2+ levels and the release of proapoptotic factors (Orrenius et al, 2003;Beech, 2005 In physiological conditions, activation of G-coupled receptors at the plasma membrane induces the release of Ca 2+ from the ER, which in turn stimuli the influx of extracellular Ca 2+ through a diversity of plasma membrane channels.…”
Section: Trp Channels and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In addition, calcium flow from the endoplasmatic reticulum (ER) is highly regulated by Ryanodine receptors, Inositol trisphosphate receptor, calciumdependent kinases, and phosphatases (Brini et al, 2014). Alterations in Ca 2 + homeostasis have been related to the appearance and progression of several NDDs, including AD and PD (Marambaud et al, 2009;Nevzati et al, 2014). Indeed, it has been reported that exposure to either Aβ peptides (Li et al, 2009) or α-synuclein oligomers (Danzer et al, 2007) induces neuronal death by activating Ca 2+ dependent signaling pathways and metabolic derangements (Arundine and Tymianski, 2003), most likely by increasing mitochondrial Ca 2+ levels and the release of proapoptotic factors (Orrenius et al, 2003;Beech, 2005 In physiological conditions, activation of G-coupled receptors at the plasma membrane induces the release of Ca 2+ from the ER, which in turn stimuli the influx of extracellular Ca 2+ through a diversity of plasma membrane channels.…”
Section: Trp Channels and Neurodegenerative Diseasesmentioning
confidence: 99%